Experience of the organization in Ukraine of the system of training of specialists for prosthetic industry according to international standards - Semenets , V.; Salieieva , A.; Avrunin , O.; Grishchenko , V.; Karpenko, I.; Solntseva , I (New Collegium, 2021)
At the present stage, the problem of training for related industries in the system of production, operation of products and provision of services is especially relevant. To a large extent, this is typical of medicine and related industries that are engaged in the production and operation of biotechnological devices and systems, electronic medical devices and the provision of rehabilitation services in health and social protection systems. Training of specialists in the field of prosthetics and orthoses for the manufacture of means for the rehabilitation of patients with musculoskeletal disorders. The aim of the work is to highlight the experience of the main stages of training of modern specialists for the prosthetic industry according to international standards. To do this, it is necessary to consider the main approaches to the formation of curricula, the organization of practical training and the scientific component of the training program for prosthetics and orthoses. From 2001 to 2012 according with cooperation program between KNURE and the Ukrainian Research Institute of Prosthetics 5 groups of bachelors and specialists with a total of 72 graduates underwent training under this program, 4 groups with a total of 65 graduates underwent retraining. In order to implement the project "Creation of prosthetic and orthopedic education in Ukraine", based on an international agreement between the Ukrainian Research Institute of Prosthetics, Kharkiv National University of Radio Electronics and the School of Rehabilitation Sciences (NS) began in January 2018 a training program for teachers-trainers for prosthetics and orthoses according to the educational program "Orthopedic Technologies and Engineering", developed in accordance with the international standard ISPO category II. The main stages of cooperation, practical and scientific parts for master’s training in the specialty "Orthopedic Technologies and Engineering" in the specialty 163 – "Biomedical Engineering" are considered. In accordance with the international standard ISPO, a program for training specialists in prosthetics and orthoses according to the scientific plan "Orthopedic Technologies and Engineering" has been created and started to operate. The perspective of the work is the development of modern educational content for the training of highly qualified specialists of different levels of education in "Orthopedic Technologies and Engineering" in accordance with modern world standards.